Acrofacial necrotic ulcers in an infant: An undiagnosed presentation - Sarika, Georgina-Maria; Shreberk-Hassidim, Rony; Maly, Alexander; Molho-Pessach, Vered (Frontiers in Pediatrics, 2022)
Acral necrotic ulcers in infancy are rare but have been described in type I interferonopathies. Herein, we present a case of an 8-year-old child who presented at the age of one month with severe ulceronecrotic lesions on the face and limbs with exacerbations following exposure to cold weather. Despite extensive investigation, the case remains undiagnosed to this day. We hypothesize that this case represents a novel and yet unknown autoinflammatory disease.